Anxiolytic effect of aqueous extract of moringa oleifera in balb/c mice - Pratiwi, Ririn Dwi; Kuswandari, Sri; Utomo, Rinaldi (Faculty of Dentistry, Universitas Islam Sultan Agung, 2023)
Background: Anxiety control is required to achieve successful dental treatment especially in children. Dental anxiety is exaggerated fear or worry associated with dental treatment and it is followed with a sense of losing control. Moringa oleifera has been claimed as a potential plant to treat anxiety. A large amount of flavonoid in Moringa oleifera leaves is known to have anxiolytic effect due to their interaction with gamma-aminobutyricacid (GABA) receptors like benzodiazepine molecule. The aim of this study was to determine the anxiolytic effect of aqueous extract of Moringa oleifera (AEMO) leaves in balb/c mice. Method: Subject of this study was 25 mice divided into 5 groups. Diazepam as a positive control (K+), CMC-Na 0.5% as a negative control (K-), aqueous extract of M. oleifera leaves 375 mg/kgBW (P1), 500 mg/kgBW (P2), and 625 mg/kgBW (P3). Tests were conducted using Elevated Plus Maze. Before and after data were analyzed with paired T-test, differences of anxiety score between groups was analyzed with One-way ANOVA. Result: Group P2 and P3 significantly reduce anxiety in mice (p